دور فتح الأذن الوسطى الاستقصائي في تقييم الأفات المرضية ضمن الأذن لدى مرضى نقص السمع التوصيلي . - يوسف, يوسف; العلوني, فايز; عمران, علي (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: due to the variety of causes leading to conductive hearing loss in the middle ear . we look for the best way of treatment these lesions , and study the prevelance . Patients and methods : 87patients underwent surgery on middle ear "exploratory tympanotomy".divided into three groups: first group "conductive hearing loss with intact membrane" second group " conductive hearing loss with tympanic membrane perforation –infection-" conductive hearing loss with tympanic membrane perforation-trauma-". Pathological observations, surgical outcome, and improved hearing were recorded in patients. Results : the most common cause of conductive hearing loss in patients with intact membrane is otosclerosis, the most common pathological lesions within the middle ear in patients with non intact membrane is granulation tissue ,fibro adhesions ,necrosis of the ossicles. Conclusions: The exploratory tympanotomy is the best choice in surgical treatment for tympanic membrane perforation and conductive hearing loss المقدمة : إن تنوع الأسباب المؤدية لنقص السمع التوصيلي ضمن الأذن الوسطى , خلف غشاء الطبل السليم أو المرضي , دفعنا للبحث عن الطريقة المثلى في علاج هذه الأفات . المواد و الطرائق : 87 مريضاً خضعوا لفتح أذن وسطى استقصائي جراحي , قُسِّموا إلى ثلاث مجموعات : الأولى (نقص السمع التوصيلي مع غشاء طبل سليم ) و الثانية (نقص سمع توصيلي مع انثقاب غشاء طبل من منشأ رضي), والثالثة (نقص سمع توصيلي مع انثقاب غشاء طبل من منشأ التهابي), تم تقييم وتسجبل المشاهدات المرضية ونتائج العمل الجراحي ومدى تحسن السمع لدى المرضى. . النتائج : إن أشيع أسباب نقص السمع التوصيلي خلف غشاء طبل سليم هو تصلب الركابة ,كما أن اشيع الموجودات المرضية المسجلة ضمن الأذن لدى مرضى انثقاب غشاء الطبل من منشأ التهابي كان النسيج الحبيبي والالتصاقات و أذية السلسلة العظمية. الاستنتاجات : يقدم فتح الأذن الوسطى الاستقصائي الخيار الأفضل للجراح للتعامل مع انثقابات غشاء الطبل وعلاج نقص السمع التوصيلي .